2015
DOI: 10.1128/mcb.00943-14
|View full text |Cite
|
Sign up to set email alerts
|

Kinase Regulation by Hydrophobic Spine Assembly in Cancer

Abstract: A new model of kinase regulation based on the assembly of hydrophobic spines has been proposed. Changes in their positions can explain the mechanism of kinase activation. Here, we examined mutations in human cancer for clues about the regulation of the hydrophobic spines by focusing initially on mutations to Phe. We identified a selected number of Phe mutations in a small group of kinases that included BRAF, ABL1, and the epidermal growth factor receptor. Testing some of these mutations in BRAF, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
151
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(160 citation statements)
references
References 29 publications
9
151
0
Order By: Relevance
“…The assembled regulatory "R spine" is the hallmark signature of an active kinase, and the disassembled-assembled R-spine switch constitutes the dynamic link between kinase inactivation-activation (5). The catalytic "C spine" is completed by binding of the ATP adenine ring that primes the kinase for catalysis (5,6). Phosphorylation of an activation loop in the large lobe forms an almost universal mechanism for EPK regulation (7,8).…”
mentioning
confidence: 99%
“…The assembled regulatory "R spine" is the hallmark signature of an active kinase, and the disassembled-assembled R-spine switch constitutes the dynamic link between kinase inactivation-activation (5). The catalytic "C spine" is completed by binding of the ATP adenine ring that primes the kinase for catalysis (5,6). Phosphorylation of an activation loop in the large lobe forms an almost universal mechanism for EPK regulation (7,8).…”
mentioning
confidence: 99%
“…A systematic evaluation of the biochemical properties of the R--spine residues and number of surrounding, "shell" hydrophobic residues confirmed that the hydrophobic nature of their side chains is essential for catalytic activity and provided other insights of value for understanding kinase regulation and of interest in the development of rational approaches to kinase drug discovery [23]. Interestingly, while the bottom two R--spine residues usually have aromatic side chains, the αC--helix R--spine residue side chain is usually Leu and mutation to bulkier Ile, Met or Phe is sufficient to drive kinase activity [24]. Displacement of the DFG motif, αC--helix and R--spine into positions incompatible with catalysis is part of the regulatory mechanism of many kinases and can also be induced by small molecule inhibitors of kinases.…”
Section: Regulatory Spinementioning
confidence: 81%
“…Once again it becomes increasingly clear that the protein kinases, like the GTPases, have evolved to be highly dynamic and regulated switches. In some cases the kinase can contribute to downstream signaling without actually transferring the phosphate while in other cases transfer of the phosphate is essential [12-15]. In either case, however, these conformational switches are highly regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Instead we must consider dynamics as an integral intermediate step that links structure and function. There are two levels of dynamics: one relates to activation and the assembly of the active kinase [12] while the other is associated with the dynamics of the catalytic cycle[16]. To understand these dynamic processes one needs to look more deeply at the conserved motifs that were initially defined.…”
Section: Introductionmentioning
confidence: 99%